PENGEMBANGAN BUKU AJAR IPS BERBASIS BUDAYA LOKAL KELAS IV SD DI KECAMATAN WIH PESAM KABUPATEN BENER MERIAH - rapita aprilia (JURNAL TEMATIK, 2017)
The research is intended to produce textbook-based IPS valid local culture with the demands of the curriculum and the local context and determine the effectiveness of the products are developed textbook. The subjects were all students in the fourth grade at SDN Blang Kucak, SDN Blang Benara and Suka Makmur. The development model used is Dick & Carey adapted to guide the development of procedures by Sa'adun Akbar. Research procedure starting from problem identification, curriculum analysis, design and deployment. The results showed that the product developed textbooks are valid through several stages of revision / repairs. The percentage of the value obtained, among others: (a) the feasibility of discussion (96%), (b) the feasibility of Contents (93%), (c) eligibility Presentation (91%), (d) practitioners 1 (94%), (e) 2 practitioners (95%), (f) the practitioner 3 (95%). For product effectiveness textbook then tested the students, following the results of the acquisition of classical percentage of student learning outcomes: (a) one to one phase of 70%, (b) the evaluation of a small group of 77.26%, and (c) limited trial 85, 71%. Based on this test, at a meeting of the three products already meet evectiveness product textbook that students achieve mastery of classical minimum of 85%.